Divergent effects of sleep efficiency and sleep medication on episodic memory in mid to late life - Amin, Suhani; Yoon, Dokyung; Naveen, Rahul; El-Magharbel, Yaseen; Vincent, Anya; Chien, Jessie Chih-Yuan; Eich, Teal S. (Frontiers in Sleep, 2026)
ObjectivesDifferent aspects of sleep quality are known to decline with age, and these changes have been shown to impact performance across multiple cognitive domains. However, despite a growing body of literature, the impact of changes to quality of sleep on episodic memory remains elusive, with some studies finding effects and others failing to find a relation.MethodsIn this study, participants [N = 173, mean age = 65.30, range = [45–88]], completed the Pittsburgh Sleep Quality Index as well as three episodic memory tests (verbal and visual episodic memory and pattern separation).ResultsWe found that worse sleep efficiency was associated with worse overall episodic memory. Further, medication use had a positive effect on verbal, pattern separation, and overall episodic memory. Findings occurred in an age-dependent manner.ConclusionsThese results underscore the complexity of sleep–memory interactions and suggest that certain aspects of episodic memory may be more sensitive to specific components of sleep quality than others, particularly as individuals age.